2022
DOI: 10.1111/jcpt.13718
|View full text |Cite
|
Sign up to set email alerts
|

PHAREO study: Perceived and observed accessibility to therapeutic drugs used for treating patients with inherited bleeding disorders

Abstract: What Is Known and Objective The dispensing of clotting factor concentrates in hospital pharmacies imposes accessibility constraints on patients and their caregivers, thereby increasing the disease burden. Very few studies have addressed these issues so far in terms of individual perceptions and actual difficulties. The PHAREO study aims to report patient's perception of treatment accessibility and evaluate spatial accessibility. Methods The PHAREO study is an observational survey based on a questionnaire speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…A recent regional observational study reported that the main determinants of dissatisfaction were parental burden (OR 2.5 [1.3; 4.8], p = .008) and waiting time at the hospital pharmacy (OR 1.5 [1.1;2.0], p = .016, per 10 min increase). 5 With 77.2% of patients without inhibitor in community pharmacy compared to 61.5% in hospital pharmacy, the comparison is borderline significant (p = .0521). 24 This difference is probably due to the fact that patients without inhibitor are less severe, and consequently more incentive and confident to choose the community pharmacy and away from the hospital professionals.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…A recent regional observational study reported that the main determinants of dissatisfaction were parental burden (OR 2.5 [1.3; 4.8], p = .008) and waiting time at the hospital pharmacy (OR 1.5 [1.1;2.0], p = .016, per 10 min increase). 5 With 77.2% of patients without inhibitor in community pharmacy compared to 61.5% in hospital pharmacy, the comparison is borderline significant (p = .0521). 24 This difference is probably due to the fact that patients without inhibitor are less severe, and consequently more incentive and confident to choose the community pharmacy and away from the hospital professionals.…”
Section: Discussionmentioning
confidence: 90%
“…Significant changes in treatment accessibility are expected by patients community and carers 2 to reduce territorial constraints 3,4 . As observed in a previous French study, both patients and hospital pharmacists pled for an evolution of the current dispensing circuit to improve access to treatment and reduce the burden of the disease, especially for active workers, parents and for patients living in rural areas 5 …”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…The availability of emicizumab in community pharmacies represents a significant advancement of the care pathway for patients with hemophilia A. The direct expected benefit concerns the improvement of the patients’ satisfaction by reducing the mental burden due to the geographical and organizational constraints to hospital pharmacies [ 8 ]. As observed in the management of other diseases, distance to the pharmacy may play a role in pharmaceutical management, leading, for example, to inappropriate and inadequate medication and management of asthma for patients living further from their preferred pharmacy [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…To maintain a sufficient level of clotting factor in the bloodstream to prevent bleeds, patients with severe hemophilia A are typically prescribed prophylactic treatment that consists of regular administration of FVIII, for example, every day, week, or month, according to how long the factor lasts in the body. Although effective, this treatment can only be administered intravenously, and in France, as well as in other countries [3][4][5][6], dispensation FVIII is only available from hospital pharmacies; they both contribute to organizational and geographical constraints [7] as well as a significant mental burden for patients and their caregivers, particularly for the parents of children with hemophilia [8].…”
Section: Introduction Backgroundmentioning
confidence: 99%